Implementasi Framework Flutter Pada Perancangan Forum Diskusi Future Sight Berbasis Android - Mochammad Wizdan Qutra tu’ain; Miftahul Jannah; Erlina (Jurnal Nasional Teknologi Komputer, 2024)
The Future Sight app is an online discussion platform designed with kids in mind. Students can utilize this application's features to create discussion groups and media for teaching and learning processes without being constrained by time, space, or distance. Students can use the Android-based Future Sight application as a platform for textual and image-based discussions, the exchange of articles, the building of friendships around online discussion topics, and statistics. The application features features such as topic creation, article creation, search, statistics, following, and followers. The Extreme Programming (XP) method was used to create this application, which has phases for planning, designing, programming, and testing. The Dart programming language, the Flutter framework, an API (application programming interface) written with Visual Studio Code as a text editor, and a MySQL database as a data storage medium were used to create the Future Sight application. Using the black box approach, the experiment produced the anticipated outcomes in line with the study's goals.